PELUANG PENGEMBANGAN BUDIDAYA MOLUSKA EKONOMIS PENTING DUSUN TAPI NEGERI WAKASIHU AMBON - Pattipeiluhu, S M; Palinussa, E M; Pattiasina, B J; Loupatty, J W; Fendjalang, S N M (Balobe: Jurnal Pengabdian Masyarakat, 2023)
Dusun Tapi Wakasihu Village has potential as a marine fishery resource, including various types of mollusks, such as abalone, lola, mata bulan, and clams. The culture of mollusks has developed in many places; however, this has not been done here. Some types can be exported, which increases income. The purpose of this community service activity is to support community groups in developing knowledge and technology of mollusk cultivation businesses with initial activities, including field assessments, socialization of the mollusk cultivation program, training and discussion sessions, and forming business groups. The development of mollusk cultivation will create opportunities for community economic development due to the availability of natural and human resources that can be fostered and assisted so that it turns to skillful community development activities in this village.